Imaging in acute stroke care: efficacy, limitations and opportunities – a systematic review - Abu Bakar, I.S.; Muda, A.S.; Ehsan, N.; Shamsuddin Perisamy, Rajeev; Kamis, M.F.A.; Tharek, A.; Ahmad Sabri, M.I.; Mahfar, N. (Longe Medikal Sdn Bhd, 2025)
Introduction: The global incidence of stroke is escalating, impacting millions annually, with acute ischemic stroke (AIS) constituting a significant proportion of cases. Modern imaging techniques have revolutionized stroke care, enabling the identification of patients eligible for reperfusion therapies, including mechanical thrombectomy (MT). However, variations in imaging workflows across healthcare systems pose challenges, leading to inconsistent clinical outcomes and treatment delays. This systematic review aims to evaluate the efficacy, limitations, and opportunities associated with recent advancements in various imaging modalities for AIS management. Method: A rigorous and transparent systematic review was conducted following established guidelines, employing the PICO (Population, Intervention, Comparison, Outcomes) framework. The search strategy focused on articles pertaining to acute stroke patients undergoing thrombectomy, workflow and techniques for radiographers, imaging modalities (CT and MRI), and patient selection and clinical outcomes. Scopus was utilized to identify relevant articles, and study selection and screening were managed using Rayyan, a web-based application. Inclusion and exclusion criteria were applied to screen articles, with a focus on studies published between 2021 and 2024. Results: The initial search yielded 157 articles, with 10 ultimately meeting the inclusion criteria after a systematic screening process. The review highlighted several key findings. Non-contrast CT (NCCT) was found to be as effective as CT perfusion or MRI for patient selection in the late window for mechanical thrombectomy. MRI acceleration techniques were identified to make MRI feasible for acute stroke imaging while retaining quality, enabling a transition from CT to MRI-based workflows. However, MRI showed lower functional independence rates compared to CT, with similar mortality and haemorrhage outcomes. CT perfusion demonstrated moderate volumetric agreement with followup DWI infarct volume, with significant overestimation in certain methods. The review also emphasized the importance of workflow optimization and multidisciplinary collaboration in optimizing imaging techniques. Conclusion: This systematic review underscores the crucial role of imaging in acute stroke management, highlighting both advancements and challenges. CT, CT perfusion, and MRI each offer unique benefits depending on the clinical situation, resource availability, and patient-specific factors.